Program Edukasi Pembuatan Jus Apel untuk Mengurangi Emesis Gravidarum Ibu Hamil Trimester I - Cut Dewi Sartika; Desi Alviolina; Indriati Aulia (Information Technology and Science (ITScience), 2025)
According to WHO (2019), the incidence of emesis gravidarum that occurs in the world varies greatly, namely 10.8% in China, 2.2% in Pakistan, 1-3% in Indonesia, 1.9% in Turkey, 0.9% in Norway, 0.8% in Canada, 0.5% in California, 0.5%-2% in America emesis gravidarum ranges from 1 to 3 percent of all pregnancies. The overall incidence ratio is 4: 1000. The incidence of nausea and vomiting in pregnant women in Indonesia ranges from 50% to 75% during the first trimester or early pregnancy. This shows that apple juice is more effective in reducing emesis gravidarum in first trimester pregnant women. Giving apple juice has proven to be effective in reducing emesis gravidarum in first trimester pregnant women at the Eliza Bestari clinic.